USEFULLNESS OF 100 MICROGRAM MISOPROSTOL IN TERM GRAVID PATIENTS REGARDING LABOUR, FETAL AND MATERNAL OUTCOME - Utman, Naeema; Akhtar, Shahnaz; Ali, Jamshid (Journal of Postgraduate Medical Institute, 2011)
Objective: To determine the effect of 100 microgram misoprostol for induction of labour in term gravid patients regarding, labour, fetal, and maternal outcome. Material and Methods: This descriptive study was carried out in the Gyne "A" Unit of PGMI/Lady Reading Hospital Peshawar, from June 2005 to February 2006. A total of 100 admitted patients were selected for the study in whom 100 microgram Misoprostol was administered orally. Labour was induced in selected patients and post delivery complications were recorded. Results: The age range of patients was from 15-39 years. Out of 100 gravid patients, primigravida were 63%. In 83% of patients pre-induction cervical scoring was <4 while 4-7 in 17% patients. Indications for induction of labour were; raised blood pressure 40%, post dates 35%, intrauterine fetal death 11%, I.U.G.R.10% and diabetes mellitus 4% cases. Misoprostol 100 microgram was given as one dose to 37% women, 2 doses to 44% women, 3 doses to 13% women, while 4 doses were given to 6% women. Normal vaginal delivery was done in 68% cases. Instrumental delivery was done in 30% cases, while cesarean section was done in 2% cases due to fetal distress. Majority of patients (69%) delivered within 24 hours. Stay in the hospital was 2 days in 42%, 3-4days in 48%, and 5-6 days in 10% of cases. Maternal complications included nausea/vomiting in 61% cases and postpartum hemorrhage in 1%. Fetal low APGAR score was observed in 6% cases. Conclusion: Oral misoprostol is an attractive alternative for induction of labour in patients with full term pregnancy.